VIRAL MARKETING MESSAGES: CONSUMER PURCHASE INTENTION TOWARDS FASHION APPAREL - Sook Fern Yeo; Cheng Ling Tan; Kah Boon Lim; Mei Ling Goh; Farah Amani Abdul Wahab (International Journal of Accounting, Finance and Business, 2020)
Due to the rapid growth of Internet usage, business sectors can gain much more benefit from it by using the Internet as a marketing tool or an advertising platform. The Internet can help a marketer, or a company promote to a large number of audiences at a lower cost. One of the effective ways to reach a large number of audiences from the Internet is by conducting viral marketing. Hence, it is essential to understand how the quality of viral marketing messages can affect customers’ purchase intentions. This study will employ the Smart-PLS 3.0 to examine to test the relationship between the factors on consumer purchase intention. Questionnaires were distributed to get responses in this study which comprised 87% of the response rate. In a nutshell, three out of four direct relationships were showing a significant positive correlation with purchase intention, namely informativeness, credibility and consumer involvement. This result indicates that entertainment has no significant relationship with the purchase intentions of consumers. Despite the useful findings that have been gathered from this study, there are some limitations found in this study. In the discussion, a summary of this study, managerial implications and new research direction are presented